A review on using inorganic binders in fiber reinforced polymer at different conditions to strengthen reinforced concrete beams. (17th October 2022) - Kirthiga, R.; Elavenil, S.
Highlights: Previous research on the strengthening of RC beam with FRCM is analyzed. Failure modes of strengthened beams are highlighted. The performances of strengthened elements with FRCM at high temperatures are reviewed. Abstract: Strengthening and rehabilitation of structural element are inevitable and the strengthened concrete structural elements are primarily used to increase the life span of deteriorated structures by complying with the updated design code and regulation. Fiber Reinforced Polymer (FRP) technique is used for repairing and strengthening concrete structures, due to the properties of FRP such as light weight, high strength, corrosion refusal and easy to oversee. The organic binder resins used along with FRP have their own shortcomings due to which inorganic binders like cementitious mortars are used along with FRP as replacement for strengthening the structural members. They are commonly denoted as Fabric Reinforced Cementitious Matrix (FRCM). Inorganic binders consist of cement mortar added with any of the industrial by-products such as fly ash, ground blast-furnace slag, silica fume etc., and relevant polymers are added to increase the bond strength virtues. The FRCM can withstand high thermal conditions and exhibits better compatibility with the concrete surface. This paper aims to provide comprehensive details about the structural strengthening using inorganic bonding agent along with FRP under common practical conditions.